Role of AIP56 disulphide bond and its reduction by cytosolic redox systems for efficient intoxication. (11th September 2019) - Pereira, Cassilda; Rodrigues, Inês S.; Pereira, Liliana M.G.; Lisboa, Johnny; Pinto, Rute D.; Araújo, Leonor; Oliveira, Pedro; Benz, Roland; dos Santos, Nuno M.S.; do Vale, Ana
Abstract: Apoptosis‐inducing protein of 56 kDa (AIP56) is a major virulence factor of Photobacterium damselae subsp. piscicida, a gram‐negative pathogen that infects warm water fish species worldwide and causes serious economic losses in aquacultures. AIP56 is a single‐chain AB toxin composed by two domains connected by an unstructured linker peptide flanked by two cysteine residues that form a disulphide bond. The A domain comprises a zinc‐metalloprotease moiety that cleaves the NF‐kB p65, and the B domain is involved in binding and internalisation of the toxin into susceptible cells. Previous experiments suggested that disruption of AIP56 disulphide bond partially compromised toxicity, but conclusive evidences supporting the importance of that bond in intoxication were lacking. Here, we show that although the disulphide bond of AIP56 is dispensable for receptor recognition, endocytosis, and membrane interaction, it needs to be intact for efficient translocation of the toxin into the cytosol. We also show that the host cell thioredoxin reductase‐thioredoxin system is involved in AIP56 intoxication by reducing the disulphide bond of the toxin at the cytosol. The present study contributes to a better understanding of the molecular mechanisms operating during AIP56 intoxication and reveals common features shared with other AB toxins.